EMPLOYEE POSITION MUTATIONS DECISION SUPPORT SYSTEM WITH AHP AND SAW METHODS - Mahdianta Pandia; Berti Sari Br Sembiring; Friendly Friendly; Zakaria Sembiring (Sean Institute, 2022)
Employees are important assets for every company, because they greatly influence many aspects of determining the success of the company's work. A company will be able to carry out all its business processes properly if all its employees can be well organized by the HR (Human Resources) section. Placement and utilization of resources in the right position is absolutely necessary. From the results of the study it can be concluded, among others: The application of a decision support system that is built can provide convenience and minimize errors that may occur in the process of determining employee positions. criteria for determining employee positions. The level of accuracy of the test results is 100%.